EFEKTIVITAS PELAKSANAAN PENDIDIKAN DAN PELATIHAN - Shinta Armayani; Connie Connie (UNIVERSITAS BENGKULU, 2020)
This research described the effectiveness of training and education implementation in Sentra Kencana Raflesia Laboratory of National family planning population council in Bengkulu province. The specific objectives of this research were to describe (1) the effectiveness of training and education program which was implemented, (2) the effectiveness of training and education implementation, (3) results’ effectiveness of training and education program implementation. This research used descriptive method with qualitative approach. The results of this research consist of: Training and education program was very effective which means that this program was implemented with “very effective indicators” were perfectly fulfilled. Training and education implementation was effective which means that this program was implemented with “effective indicators” complied. The results’ effectiveness of training and education program was adequate because it was suitable with adequate effectiveness criteria. To sum up, generally, the effectiveness of training and education implementation in Sentra Kencana Raflesia Laboratory of National family planning population council in Bengkulu province was effective.